2001
DOI: 10.1088/0953-8984/13/5/315
|View full text |Cite
|
Sign up to set email alerts
|

First-principles studies of the stability of Zintl ions in alkali-tin alloys: II. Liquid alloys

Abstract: Following our preceding work on the structure and electronic properties of crystalline Zintl phases in alkali-tin systems, we have studied the structural, dynamic and electronic properties of these alloys in the molten state using ab initio local density functional molecular dynamics. Extended simulations (up to 124 atoms per cell, simulation times of up to 60 ps) have been performed for K-Sn, in which, according to the results for the crystalline compounds, the tetrahedral Sn4 polyanions can be expected to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 54 publications
(89 reference statements)
1
9
0
Order By: Relevance
“…Indeed, the first peak minimum is markedly deep, even approaching zero for the systems alloyed with large alkali atoms. 12,14 We have found a number of arguments favoring the formation of stable Hg n polyanions, the strongest one being the lack of dependence on composition of the g Hg-Hg (r) low r region. In other systems, e.g., K-Pb alloys, it has been suggested 14 that Zintl structures are progressively stabilized when approaching central compositions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the first peak minimum is markedly deep, even approaching zero for the systems alloyed with large alkali atoms. 12,14 We have found a number of arguments favoring the formation of stable Hg n polyanions, the strongest one being the lack of dependence on composition of the g Hg-Hg (r) low r region. In other systems, e.g., K-Pb alloys, it has been suggested 14 that Zintl structures are progressively stabilized when approaching central compositions.…”
Section: Resultsmentioning
confidence: 99%
“…Both group-IV-alkali and Hg-alkali [9][10][11] crystalline phases exhibit polyanion units. It has been shown that these units are preserved in liquid group-IV-alkali alloys, 12 for which transport properties are closely related to those of Hg-alkali alloys. 3,13 It has been proposed 12-14 that the formation of polyanion, Pb 4 4Ϫ is responsible for this maximum of resistivity at 50 at.…”
Section: Introductionmentioning
confidence: 99%
“…The VASP code makes use of ultrasoft pseudopotentials [18], and an expansion of the electronic wave functions in plane waves. The approach has been applied widely in AIMD simulations of liquid metals and alloys [19][20][21][22][23][24][25][26][27]. Our simulations were performed using a cubic supercell containing 128 particles with periodic boundary conditions and C-points sampling.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…The main problem with simulations of such complicated liquids like those of the Zintl-type is the huge computational demand. First ab initio MD simulations of the structure and vibrational properties of liquid K x Sb 12x [15] or Na x Sn 12x [16] used relatively small cells and were made over short simulation times. To get a converged static structure factor or even the S ij (Q, v)s at small Q one would need several orders of magnitude more computer power.…”
Section: Resultsmentioning
confidence: 99%